Impact of total marrow/lymphoid irradiation dose to the intestine on graft-versus-host disease in allogeneic hematopoietic stem cell transplantation for hematologic malignancies - Saldi, Simonetta; Fulcheri, Christian Paolo Luca; Zucchetti, Claudio; Abdelhamid, Amr Mohamed Hamed; Carotti, Alessandra; Pierini, Antonio; Ruggeri, Loredana; Tricarico, Sara; Chiodi, Marino; Ingrosso, Gianluca; Bini, Vittorio; Velardi, Andrea; et al. (Frontiers in Oncology, 2022)
Background and purpose Graft-versus-host disease (GvHD) is a leading cause of non-relapse mortality in patients undergoing allogeneic hematopoietic stem cell transplantation. The Perugia Bone Marrow Transplantation Unit designed a new conditioning regimen with total marrow/lymphoid irradiation (TMLI) and adaptive immunotherapy. The present study investigated the impact of radiotherapy (RT) doses on the intestine on the incidence of acute GvHD (aGvHD) in transplant recipients, analyzing the main dosimetric parameters. Materials and methods Between August 2015 and April 2021, 50 patients with hematologic malignancies were enrolled. All patients underwent conditioning with TMLI. Dosimetric parameters (for the whole intestine and its segments) were assessed as risk factors for aGvHD. The RT dose that was received by each intestinal area with aGvHD was extrapolated from the treatment plan for each patient. Doses were compared with those of the whole intestine minus the affected area. Results Eighteen patients (36%) developed grade ≥2 aGvHD (G2 in 5, G3 in 11, and G4 in 2). Median time to onset was 41 days (range 23–69 days). The skin was involved in 11 patients, the intestine in 16, and the liver in 5. In all 50 TMLI patients, the mean dose to the whole intestine was 7.1 Gy (range 5.07–10.92 Gy). No patient developed chronic GvHD (cGvHD). No dosimetric variable emerged as a significant risk factor for aGvHD. No dosimetric parameter of the intestinal areas with aGvHD was associated with the disease. Conclusion In our clinical setting and data sample, we have found no clear evidence that current TMLI dosages to the intestine were linked to the development of aGvHD. However, due to some study limitations, this investigation should be considered as a preliminary assessment. Findings need to be confirmed in a larger cohort and in preclinical models.